Transcranial ultrasound in the critically ill patient: a narrative review - R. M. J. Cashmore; M. Czosnyka (Intensive Care Medicine Experimental)
Abstract Transcranial ultrasound is gaining widespread recognition as a useful bedside monitoring tool and non-invasive diagnostic device in the critically ill patient. The capabilities of transcranial ultrasound are themselves ever-increasing, and this, combined with improved physiological understanding, affords insights into pathophysiological processes often concealed from the bedside critical care clinician. Transcranial ultrasound remains unique in regard to its non-invasive, rapid, and critically composite blood flow velocity-centric (not pressure-centric) information. The mobility of transcranial ultrasound devices is of particular value to the largely immobile critically ill patient requiring multiple organ supportive therapies. In this review, we discuss some important origins of more modern composite techniques and highlight relevant major key concepts, whilst noting exciting frontier possibilities.